Stylistics Analysis Of National Geographic Magazine’s Cover June Edition - Ariwibowo, Vincentius Seto (Universitas Islam Negeri (UIN) Salatiga, 2021)
This research presented the Stylistics analysis of National Geographic magazine’s cover June edition. The magazine was chosen because it is one of the magazine's newest issues by the time the researcher conducting this research. The Stylistic approach was employed to understand and reveal the magazine editor's purposes in using specific language and visual features. Considering this research analyzes visual feature; therefore, the theory of visual grammar was employed. To achieve the analysis's goal, the researcher analyzed the language features from three language levels and a feature from visual grammar. In the level of phonology, the features are assonance, alliteration, and consonance. In the level of graphology, the features are italicization, uppercase, and lowercase. In the level of typography, the features are font size and the position of the text. In the visual grammar, the feature is distance. The researcher found that the language and visual features are used in purposes. They were used to give some effects to the reader that can attract them to read the magazine. In conclusion, the stylistics was proven in revealing the editor’s purposes of using language and visual feature in the magazine cover. Keywords: stylistics, visual analysis, magazine cover